Patterns in Shakespearian tragedy - Ribner, Irving (Routledge library editions. Shakespeare., 2004)
First published in 1960. Patterns in Shakespearian Tragedy is an exploration of man's relation to his universe and the way in which it seeks to postulate a moral order. Shakespeare's development is treated accordingly as a growth in moral vision. His movement from play to play is carefully explored, and in the treatment of each tragedy the emphasis is on the manner in which its central moral theme shapes the various elements of drama.